Economic, energy and carbon footprint assessment of integrated forward osmosis membrane bioreactor (FOMBR) process in urban wastewater treatment. Issue 1 (19th November 2019) - Ab Hamid, Nur Hafizah; Smart, Simon; Wang, David K.; Koh, Kaniel Wei Jun; Ng, Kalvin Jiak Chern; Ye, Liu
Abstract : This study systematically explores the potential applications of forward osmosis (FO) membrane based technology in urban wastewater treatment and water reclamation for their techno-economic feasibility and sustainability. Abstract : The application of forward osmosis (FO) membrane-based technology in urban wastewater treatment has received increased attention, however, its techno-economic feasibility and sustainability have not been fully demonstrated. In this study, the feasibility of FO application in urban wastewater treatment was assessed in terms of economic performance, energy consumption and greenhouse gas (GHG) emissions benchmarked against microfiltration (MF). Three different scenarios of wastewater treatment and water reclamation were proposed: (A) forward osmosis aerobic membrane bioreactor (FOAeMBR); (B) FOAeMBR integrated with reverse osmosis (RO); (C) forward osmosis anaerobic membrane bioreactor (FOAnMBR) integrated with partial nitrification/anammox (PN/AMOX) process. In this study, the wastewater treatment and reclamation costs by using FO in scenarios A and B were more expensive than MF by 0.16 per m 3 and 0.75 per m 3 respectively due to the larger surface area of FO membrane required. In scenario C, the wastewater treatment cost of using FO (1.11 per m 3 ) was equivalent to MF. This was due to the good rejection performance of FO and its ability to concentrate wastewater, hence, resulting in a higher efficiency of (PN/AMOX) in comparison to MF. In addition, the application of FO in scenario C generated total GHG emissions to be as low as 0.93 kg CO2 equivalent m −3, which was 1.5 and 4.1 times lower than scenarios A and B respectively. The minimal net energy consumption and low carbon footprint of FO application in scenario C suggests this integration will likely be a feasible membrane-based technology for the next generation of wastewater treatment.